A Checklist of Fishes of Mahanadi River, India - Lalit Kumar Tyagi; Rejani Chandran; Sangeeta Mandal; Trivesh Suresh Mayekar; Amit Singh Bisht; Sanjay Kumar Singh; Kuldeep Kumar Lal (Journal of Indian Fisheries Association, 2021)
Present findings provide a checklist of fishes of Mahanadi River, an important peninsular river of India. A total of 16 seasonal field explorations were conducted at 40 sites in entire stretch of Mahanadi from its origin in Chhattisgarh to its exit into Bay of Bengal during the period from November, 2012 - September, 2018. A total of 121 fish species from 21 orders, 43 families and 85 genera were recorded from the river. Cypriniformes represented by 49 species, was found to be the most dominant order (40%) followed by Siluriformes with 23 species (19%). Cyprinidae was the richest family (33 species) followed by Danionidae (11 species) and Bagridae (7 species). Out of 121 fish species reported, 66 species were food fishes, 22 had ornamental importance while 33 species had both food and ornamental importance. The present checklist prepared from extensive sampling and exploratory surveys across the entire stretch of Mahanadi shall be helpful in monitoring and drawing up eﬀective conservation strategies.